2014
DOI: 10.3892/etm.2014.1916
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a novel splice variant of FRMD7 in developing human fetal brains that is upregulated upon the differentiation of NT2 cells

Abstract: FRMD7 mutations are associated with X-linked idiopathic congenital nystagmus (ICN); however, the underlying mechanisms whereby mutations of FRMD7 lead to ICN remain unclear. In a previous study, the first FRMD7 splice variant (FRMD7-S) was cloned and identified, and FRMD7-S was hypothesized to play a significant role in neuronal differentiation and development. The present study investigated a novel multiple exon-skipping mRNA splice variant of FRMD7, termed FRMD7_SV2, which was detected in NT2 cells using nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…It is also selectively expressed in starburst amacrine cells ( 7 , 27 , 28 ). It is involved in the regulation of eye movement, neuronal morphogenesis, synapse function, and neurite growth ( 29 ). The FERM domain and the FERM-adjacent domain control plasma membrane and actin cytoskeleton organization suggesting that they are essential to the development of neural system and the brain region that control eye movement ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also selectively expressed in starburst amacrine cells ( 7 , 27 , 28 ). It is involved in the regulation of eye movement, neuronal morphogenesis, synapse function, and neurite growth ( 29 ). The FERM domain and the FERM-adjacent domain control plasma membrane and actin cytoskeleton organization suggesting that they are essential to the development of neural system and the brain region that control eye movement ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several FRMD7 isoforms have been shown to play important roles during neuronal differentiation and development. The original form of FRMD7 (FRMD7-FL) and its splice variants FRMD7-S and FRMD7_SV2 are involved in the neuronal development process ( 29 ) ( 31 ). A search performed on the BLAST tool showed that the FRMD7 protein shared a close homology with FARP1 and FARP2, which modulate the length and the degree of branching of neurites in rat embryonic cortical neurons and reorganize the cytoskeleton ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…This variant form may be important in the context of neuronal differentiation and development [ 24 ]. Another splice variant, FRMD7 ( FRMD7_SV2 ), is similarly predicted to be important for neuron development [ 25 ]. The FRMD7 mutation of c. 206-5 T > A is predicted to disrupt the splice acceptor site in the third intron, while variant c.205 + 2 T > G is predicted to be pathological on the basis of its likelihood to induce nonsense-mediated decay or exon skipping [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Variants in FRMD7 account for approximately 70% of known IIN cases ( Tarpey et al, 2006 ) ( Salman et al, 2022 ). Though the function of FRMD7 is not yet fully understood, it is expressed in both the developing neural retina and ocular motor structures such as the cerebellum and vestibular-optokinetic system, playing a role in the control of eye movement and gaze stability, as was recently confirmed by Salman et al in the starburst amacrine cells of mutant Frmd7 tm1a and Frmd7 tm1b mouse models ( Almoallem et al, 2015 ) ( Tarpey et al, 2006 ) ( Choi et al, 2018 ) ( Li et al, 2014 ) ( Pu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 89%